Cross-cultural adaptation and validation of the VISA-P questionnaire for Portuguese-speaking (Portugal) patients with patellar tendinopathy. (24th June 2020) - Chaves, P; Ribeiro, D; Gomes, J; Monteiro, M; Marote, S; Frutuoso, S; Araújo, FA; Paço, M
Abstract: Introduction Patellar tendinopathy is a condition frequently verified in individuals who practice regular physical activity, therefore functional evaluation is crucial to monitor symptoms. The VISA-P was developed for English-speaking population to evaluate patients with this condition, and there is a need to adapt this tool to Portuguese (Portugal). Objectives To cross-cultural adapt and validate the VISA-P questionnaire for Portuguese-speaking (Portugal) patellar tendinopathy patients Methodology The VISA-P questionnaire was translated and cross-culturally adapted into Portuguese (VISA-P-Por) according to specific guidelines, using six steps: Translation, synthesis, back translation, expert committee review, pretesting (n = 10), and appraisal of the adaptation process. The resulting VISA-P-Por was then subjected to an analysis of the psychometric properties (construct validity, reproducibility [agreement and reliability], internal consistency and floor and ceiling effects) in 73 patellar tendinopathy patients and 73 asymptomatic people. Participants completed the questionnaire at baseline and after a minimum interval of 48 hours. Results The Visa-P-Por questionnaire revealed a high level of agreement, presenting semantic and content validity. Construct validity showed differences between both groups (p < 0, 001) and the questionnaire exhibited very good internal consistency, with an excellent α Cronbach (0, 91). Concerning reproducibility, agreement levels were considered optimal which can be proven by the Bland Altman graph, the standard error of measurement (5, 74) and the minimally important change (15, 91 points), as well as the excellent ICC value (0, 92). There were no ceiling and floor effects detected. Conclusion The VISA-P-Por questionnaire is a valid and reliable tool, with psychometric properties comparable with the original version. Thus, it can be recommended as a robust tool for measuring clinical severity and functional impact of patellar tendinopathy in Portuguese-speaking (Portugal) patients.